Penerapan Metode SWOT dan BOS dalam Menilai Peluang Usaha Sempol Ayam di Kota Mataram - Kurnia, Fikrihadi; Pradityatama, Maharsa (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
MSMEs are productive businesses managed by individuals, groups, households, or small business entities that are realized according to assets and / or sales profits per year. The culinary industry is a type of MSME that has a fairly broad market. One of them is a traditional snack business that is quite popular in the community with low prices and raw materials that are easily obtained is chicken sempol. Sales of chicken sempol are dominated by micro and small enterprises. An effective strategy by MSME owners is needed through the use of SWOT (Strength, Weakness, Opportunity, Threat) and BOS (Blue Ocean Strategy) methods. SWOT aims to analyze the internal and external conditions of MSMEs, while BOS aims to improve product quality and innovation so that petitions can be minimized. This service activity will be carried out in October 2023, at MSMEs Cilok vs Sempol Goyang Senggol, Jl. Panji Tilar Negara, Kekalik, Mataram City, West Nusa Tenggara. The results of the analysis show that it is necessary to evaluate product quality, flavor variants, and marketing strategies. Based on this evaluation, it becomes a strategy by MSME owners in considering it as a variable to be innovated in marketed products.